LIVRE EXPRESSÃO LÚDICA GRUPAL COMO ESTRATÉGIA DE ENFRENTAMENTO EM CRIANÇAS NEGLIGENCIADAS - SOUZA, FRANCISCA YANA BIZERRA ALVES DE (2020)
The specialized literature indicates that negligence is the most recurrent form of abuse against children and adolescents. Studies indicate that neglected children can accumulate multiple problems in their development and in their adaptive capacities, with violence being experienced in a unique way, depending on a multiplicity of factors of a personal nature. The creative process can be seen as one of the possibilities to overcome a traumatic situation, since this is defined as the ability to create vital alternatives. Considering playing as an example of greater creativity and integral development of being, it is possible to say that free playful expression can contribute to the perception that the child has about himself and his experience of neglect, increasing self-esteem and promoting his emotional and affective. It is a descriptive exploratory study with a qualitative character, whose objective was to evaluate and relate psychodynamic aspects of children victims of neglect before and after the intervention process based on free playful group workshops. The sample consisted of seven children, of both sexes, sent to an institutional care unit by court order or guidance from the Guardian Council, exclusively because the possibilities of maintenance within the family were exhausted. The sample was selected in a non-probabilistic, casual way, according to convenience. The Human Figure Drawing (DFH) and the Person in the Rain (DPC) Drawing were used as instruments, both applied individually before and after the group workshops that used the Pichon-Rivière Operative Group technique as a conceptual reference. Eight group meetings were held and analyzed using the parameters offered by the Referential and Operational Conceptual Scheme (ECRO). The data obtained by the instruments applied in the initial and final stages were understood together with the process triggered by the workshops carried out in groups, being analyzed based on contributions from group psychoanalysis and psychoanalysis itself for the analysis of the results of the applied instruments. The proposal of the free expression group workshop proved to be mobilizing, allowed the emergence and elaboration of poorly integrated aspects related to life inside and outside the shelter, and its application in institutional contexts as relevant in this study was relevant. The performance of free expression activities in groups can be a tool that promotes health in this segment of the population, avoiding their illness and the compromise of important aspects of child development and, therefore, minimizing the suffering of these children.